2022
DOI: 10.1186/s40643-022-00524-4
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution driving the generation of an efficient keratinase variant to facilitate the feather degradation

Abstract: Keratinases can specifically degrade keratins, which widely exist in hair, horns, claws and human skin. There is a great interest in developing keratinase to manage keratin waste generated by the poultry industry and reusing keratin products in agriculture, medical treatment and feed industries. Degradation of keratin waste by keratinase is more environmentally friendly and more sustainable compared with chemical and physical methods. However, the wild-type keratinase-producing strains usually cannot meet the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Notable, fibers of BC produced by EDCFs medium diameters were found to be an average of 50–100 nm, whereas diameters of bacterial cellulose produced by HS medium were found to be between 100–150 nm. The current SEM investigation is almost consistent with SEM investigations as previously reported by Tsouko et al 53 and Zhang et al 54 .
Figure 6 SEM image of BC obtained from HS medium ( A ) and from EDCFs based medium ( B ) at magnification power 20,000X.
…”
Section: Resultssupporting
confidence: 92%
“…Notable, fibers of BC produced by EDCFs medium diameters were found to be an average of 50–100 nm, whereas diameters of bacterial cellulose produced by HS medium were found to be between 100–150 nm. The current SEM investigation is almost consistent with SEM investigations as previously reported by Tsouko et al 53 and Zhang et al 54 .
Figure 6 SEM image of BC obtained from HS medium ( A ) and from EDCFs based medium ( B ) at magnification power 20,000X.
…”
Section: Resultssupporting
confidence: 92%
“…Keratinases (EC 3.4.-.-) are a type of proteases with unique hydrolytic properties. They enable the degradation of hard keratin waste into high value-added products such as soluble proteins, amino acids, and bioactive peptides. , To date, research on keratinases has mainly focused on the mining of new keratinases and the modification of enzyme properties. Previously, the keratinase gene of Bacillus licheniformis was successfully expressed in Bacillus subtilis to obtain the highly active keratinase enzyme KerZ1 . Recently, Peng et al achieved improved KerZ1 expression and 188.1-fold increased activity compared with that of the wild enzyme by optimizing the promoter sequence and ribosome binding site (RBS) .…”
Section: Introductionmentioning
confidence: 99%
“…subtilis 168 also increased the expression of β-galactosidase and nattokinase . Knockout of autolysis-related genes lytC and sigD effectively increased exogenous protein production and delayed autolysis by 10–15 days. It is worth noting that not all deletions of autolysis genes are positive. For example, when the peptide chain endopeptidase genes lytE and lytF were individually deleted, the mutants exhibited growth division defects but were not effective in inhibiting cellular autolysis .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Researchers have done extensive studies on the efficient heterologous expression of keratinase and found that B. subtilis is an excellent expression host. 15,20,21 We have successfully expressed keratinase derived from B. licheniformis BBE11-1 in B. subtilis WB600 and enhanced the expression of keratinase by promoter optimization, RBS sequence screening, and lead peptide engineering strategies. 22−24 It is worth noting that the low titer of recombinant keratinase in B. subtilis remains the main problem limiting its industrial application, and cellular autolysis may be one of the important reasons hindering the enhancement of enzyme protein titer.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation